1989
DOI: 10.1073/pnas.86.24.10064
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of src family gene for tyrosine-kinase p59fyn in CD4-CD8- T cells of mice with a lymphoproliferative disorder.

Abstract: Overexpression of a src family gene, lck, has been associated with differentiation of the murine thymic lymphoma line LSTRA. Recent findings by several groups strongly suggest a functional role for the gene product p56lck protein-tyrosine kinase (PTK) in the activation of normal T cells. A single recessive gene, lpr or gld, induces a lymphoproliferative disorder concomitant with autoimmune disease in mice. In this study, a 10-fold elevated activity of PTK encoded by fyn, another src family gene, was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…However, any deficit observed in peripheral lprllpr T cells is probably not the by-product of constitutive tyrosyl phosphorylation by fyn kinase, because fyn activity is not overexpressed in these cells (36). In contrast, no similar analyses of PTK activities have yet been reported in human lupus T cells, and we therefore do not know whether a disorder of PTK-catalyzed protein phosphorylation exists in human lupus T cells.…”
Section: Aberrant Receptor-mediated Signal Transductionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, any deficit observed in peripheral lprllpr T cells is probably not the by-product of constitutive tyrosyl phosphorylation by fyn kinase, because fyn activity is not overexpressed in these cells (36). In contrast, no similar analyses of PTK activities have yet been reported in human lupus T cells, and we therefore do not know whether a disorder of PTK-catalyzed protein phosphorylation exists in human lupus T cells.…”
Section: Aberrant Receptor-mediated Signal Transductionmentioning
confidence: 82%
“…Unstimulated C3H-lpr/lpr DN T cells obtained from lymph nodes demonstrated markedly increased, constitutive tyrosyl phosphorylation of the 16-kd Sand 21-kd 7 subunits of CD3 when compared with normal C3H +/+ T cells (35). Subsequently, it was found that the src nonreceptor protein tyrosine kinase (PTK), p59fy", may be mediating this effect, because it is overexpressed in DN T cells (36) (Figure 1). The significance of this novel observation is that the fyn kinase is associated with the CD3/T cell receptor (TCR) complex, and directly mediates the signal initiated by ligand binding (37,38) (Figure 1).…”
Section: Aberrant Receptor-mediated Signal Transductionmentioning
confidence: 99%
“…However, Fyn is known to be overexpressed in CD4 Ϫ CD8 Ϫ T cells from MRL/lpr mice that have an abnormal proliferative capacity and exhibit altered TCR signal transduction pathways (18). Moreover, increased Fyn kinase activity was shown to correlate with maintenance of the anergic state in T cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, an elegant study in MRL/lpr mice has demonstrated that the mouse homologue of the T cell receptor (TCR) z chain is constitutively and strongly phosphorylated, while the g-chain homologue is not phosphorylated, even by stimulation with TCR cross-linking. Moreover, these abnormalities have been shown to be partly the result of increased expression and phosphorylation of p59 fyn in MRL/lpr mice [10]. Given the recent finding that a principal genetic defect in MRL/lpr mice is a mutation in the Fas gene, the question should be addressed whether the altered signal transduction via TCR/CD3 is secondary to the mutation or not.…”
Section: Introductionmentioning
confidence: 99%